The role of professionals in partnership-based urban upgrading interventions - Malan, Johanna (Department of Civil Engineering, 2019)
In South Africa, current urban planning models and traditional state-led urban interventions seem to have noticeably failed to sustainably address the integrated problems that are evident in informal settlements throughout the country. In the case of many current urban interventions, professionals give technocratic solutions to problems in informal communities with little to no consultation or engagement with the affected community. The result is often that community's needs are not sufficiently met and the community is not capacitated to take full ownership of the solution. More often than not the intervention (technocratic solution) becomes mismanaged, underutilised and inevitably the solution is proven to be unsustainable. This phenomenon has highlighted the need for a new approach to addressing the needs of informal settlement dwellers. In recognition of the need for a new approach, this case study of a partnership-based urban upgrading intervention is conducted in order to make realistic recommendations regarding the value of professionals in partnership-based urban upgrading interventions as opposed to top-down interventions. The primary research question of this case study is thus: what lessons can be learnt about the role of the professional in partnership-based urban upgrading interventions by gaining insight on a successful partnership-based intervention? The Genius of SPACE (GOS) partnership, based in the informal settlement of Langrug in the Stellenbosch Municipality is used as the topic of the case study to answer the research question. The GOS partnership was initially formed to address greywater management and stormwater drainage challenges in the settlement. A capability analysis approach is utilised as a theoretical tool to investigate all of the different assets which might be available to the professional to contribute to addressing the social as well as the technical challenges that the GOS partnership aims to address. This tool ultimately contributes to the development of clear guiding principles for technical professionals working in urban upgrading partnerships. Some key guidelines for technical professionals in partnerships emerge from the case study and clearly show that a developmentally aligned partnership should ultimately be able to utilise not only technical abilities and skills but also social expertise to facilitate community mobilisation strategies that allow for highly responsive upgrading processes to ensure long-lasting structural as well as social change.